CP-075 Prognostic factors in patients with recurrent epithelial ovarian cancer. (25th February 2017) - Palomo, A Rodriguez; Manceñido, FJ Alvarez; García, I Zapico; Lorenzo, L Sanchez; Villanueva, P Pena; Bayonas, A Carmona; Canovas, M Sanchez; Faez, L; Solis, MP; Fonseca, P Jimenez
Abstract : Background: Pegylated liposomal doxorubicin (PLD) is indicated in ovarian cancer patients who have failed firstline platinum based chemotherapy. Currently, there are no clinical or biomolecular factors that can predict the benefit of PLD in this population. Purpose: To identify clinical predictors of overall survival (OS) in patients with recurrent ovarian cancer treated with PLD. Material and methods: 9 baseline variables were evaluated to assess its prognostic ability in 143 patients treated with PLD from January 2008 to January 2014. The analysed variables were: Eastern Cooperative Group Performance Status (ECOG-PS), age, histopathology, treatment line, platinum sensitivity (progression free interval(PFI)) and chemotherapy schedule (monotherapy vs polychemotherapy). Cox regression models were used to calculate the log hazard ratio, and the most parsimonious model was selected according to the Akaike information criteria. Results: The prognostic index includes four variables associated with OS: ECOG-PS (>70), age (≤70 years), platinum highly sensitive (PFI ≥12 months after completion of frontline platinum based chemotherapy) and use of combination chemotherapy (PLD and carboplatinum/gemcitabine/trabectidin were assigned 2 points and intermediately sensitive (PFI 6–12 months) was assigned 1 point). The global median progression free survival for all patients was 5.9 months (95% CI 4.0–7.3) and median OS was 18.8 months (95% CI 15.2–23.3). The score had the potential to delineate five prognostic groups whose results are shown in the table. Conclusion: Young age (<70 years), good performance status, platinum sensitivity and PLD based polychemotherapy proved to be predictive and prognostic factors. Therefore, these factors should be considered when making decisions about the approach to these patients. Nevertheless, this preliminary evidence must be validated in a prospective clinical trial. No conflict of interest